Exploitation of inventions in competitive advantageous producing sectors: actual status and policy solutions. - Xuyen, Nguyen Huu (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Exploitation of inventions plays important roles for sustainable development of enterprises, particularly in those sectors which hold competitive advantages. In Vietnam, activities of exploitation of inventions among enterprises in recent times remain limited and existing policies do not really stimulate enterprises to promote application and exploitation of inventions. These limited actions cause considerable negative impacts to creation of new and high quality products possibly commercializable for exportation purpose. This paper targets to clarify various aspects of the matter and to provide answers to the following questions: (i) What are competitive advantageous producing sectors and the exploitation of inventions in competitive advantageous producing sectors? (ii) Which is the actual status of activities of exploitation of inventions in competitive advantageous producing sectors? (iii) What would be policy based solutions the Government and the State should issue to push up activities of exploitation of inventions in competitive advantageous producing sectors in conformity to actual conditions of Vietnam? Code: 16082701 <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">